Introduction to Kris, a traditional weapon of Indonesia: Preserved-lingering issues of facts - Sugeng Purwanto; Idha Nurhamidah (Universitas Islam Sultan Agung, 2021)
The current article examined some issues on Kris, a traditional weapon of Indonesia as a high cultural heritage, which is up to now still preserved with all of its manifestations. A Kris may be viewed from its definition, magical charms, parts, elements, maintenance, symbolic values, philosophical meanings, production periods and legendary preservation. Ethnolinguistic investigation revealed that Kris has significantly contributed to the lexical domain, hereinafter referred to as Kris Registers. There are a lot of registers related to its entity, which are of great difficulty for lay people to understand, except those who are really involved in the world of Kris, such as Kris masters (makers), parapsychologist, antiques collectors, cultural researchers to mention only a few. A cultural fact has been identified—that it is the owners’ ways of life in addition to their personal characteristics. One important recommendation of Kris with its all manifestations is that it has to be preserved as an asset of high cultural values through one person one Kris program.